Ingensin, a fatty acid-activated serine proteinase from rat liver cytosol - Ishiura, Shoichi; Yamamoto, Takeshi; Nojima, Michio; Sugita, Hideo (Biochimica et biophysica acta, 1986)
The enzyme responsible for the succinylleucyllvalytyrosine methylcoumarylamide- (SLLVT-) degrading activity was purified from the postmitochondrial supernatant of rat liver (Yamamoto, T., Nojima, M., Ishiura, S. and Sugita, H. (1986) Biochim. Biophys. Acta 882, 297–304). The enzyme, named ingensin, was activated by saturated fatty acids, especially myristic acid, as well as by unsaturated linoleic acid and arachidonic acid. Although 2-mercaptoethanol activated ingensin 2-fold and p-chloromercuribenzoate and HgCl 2 completely inhibited its peptide-hydrolyzing activity, the enzyme is activated by the addition of a thiol-blocking reagent, monoiodoacetic acid. Ingensin was also inhibited by a specific serine proteinase inhibitor, diisopropyl fluorophosphate, but not by a specific cysteine proteinase inhibitor, E-64-c. These results suggest that the enzyme is a serine proteinase with an active thiol group(s) near the active site. We have found that the addition of glycerol and nordihydroguaiaretic acid lowered the extent of its activation by fatty acids as well as its intrinsic peptide-hydrolyzing activity.